(untitled) (Diversity Research: Journal of Analysis and Trends, 2025)
The article discusses measures of state support for small business and entrepreneurship in Uzbekistan aimed at stimulating economic growth and developing the private sector. Special attention is paid to the mechanisms of state assistance, including tax incentives, subsidies, loans, as well as the creation of favorable conditions for the development of start-ups and innovative companies. The study shows that the successful implementation of these programs contributes not only to an increase in the number of small and medium-sized enterprises, but also to an increase in the competitiveness of the country’s economy, with a possible increase in statistics by 5.6%. The article also analyzes the prospects for improving government support in the context of globalization and digitalization.